Follicular lymphoma in the third eyelid in a feline: A case report of a rare neoplasm associated with co-infection viral by calicivirus, FIV and FeLV (Research, Society and Development, 2021)
Lymphoma represents about 80% of hematopoietic tumors in felines, being diagnosed through cytopathological, histopathological and immunohistochemical analyses. Classification follows anatomical location (gastrointestinal, mediastinal, nodal and extranodal) and grade (low, intermediate and high). We aimed to report a rare case of lymphoma in a domestic feline, male, 8 years old, not vaccinated, not neutered, semi-domiciled and from a socially vulnerable community. Upon clinical examination, the feline showed thin body condition, apathy, dehydration, pale mucosa, reactive submandibular and retropharyngeal lymph nodes, bilateral ocular secretion, exophthalmia, facial lesion and edema, third eyelid prolapse, diffuse skin nodules and evidence of pain. Laboratory tests confirmed that the feline was positive for feline immunodeficiency virus (FIV), feline leukemia virus (FeLV) and calicivirus, fungi and bacteria were identified in the eye sample, the blood count showed anemia, thrombocytopenia, leukopenia and lymphopenia. The patient died after the initial approach, without establishing a therapeutic protocol to treat the neoplasm. The histopathological diagnosis after tumor examination was follicular lymphoma in the third eyelid, with the presence of neoplastic lymphocytic cells with moderate pleomorphism and sparse cytoplasm distributed in loose connective tissue. Follicular lymphoma in the third eyelid of felines is rare, however, it is likely that semi-domiciled animals without vaccine immunization are more likely to develop this type of neoplasm due to viral oncogenic action associated with co-infection with FIV and FeLV.